The Involvement of Students’ Parents in Organizing the Learning from Home at Elementary Schools in Tomohon City - Tamboto, Heidy; Tambingon, Henny N.; Lengkong, Jeffy S.J; Rotty, Viktory Nicodemus Joufree (Asia Pacific Journal of Management and Education (APJME), 2021)
Fulfilling the rights of students to get educational services during the spread of the Corona Virus (COVID-19) is pursued through the implementation of Learning from Home policy. Parental involvement has a crucial influence on students’ involvement. This study aims to analyze and explain the involvement of students’ parents in implementation of learning from home in elementary schools in Tomohon City. This study applies a qualitative approach, case study methods, data collection techniques in the form of interviews, observation, and documentation as well as qualitative data analysis techniques adapted from interaction models. The results showed that the parents of students were very actively involved, especially from the mother's side, the forms of involvement were physical and non-physical, and there was personal communication between parents and teachers. In addition, a lack of readiness, cost, time, and teaching knowledge from students’ parents identified as an inhibiting factor which is overcome by providing opportunities for involvement, interpersonal communication and coordination and provision of incentives. Conclusions and suggestions for future research related to the importance of examining the parental involvement process of students are also presented at the end of the chapter.